Experience of Thai Nurses’ Work During Pregnancy: A Qualitative Descriptive Research - Preeyakamon Krikitrat; Petsunee Thungjaroenkul; Wongduean Chaiwipassatorn; Crystal L. Patil (International Nursing Review, 2026)
ABSTRACT Aim To explore the experiences of Thai nurses who work while pregnant, focusing on their perceptions of workplace support and obstacles, and how these factors affect their health. Introduction Pregnant nurses in Thailand often continue working in demanding hospital environments, facing physical, chemical, and biological hazards that may affect both maternal and fetal health. Despite existing labor regulations, maternity protections are limited in government hospitals, and job adjustments are rarely implemented. Methods A descriptive qualitative design was used with purposive and snowball sampling. Data were collected between October 2024 and May 2025 through face‐to‐face, semi‐structured interviews with 26 registered nurses in their first to third trimesters, recruited from hospitals in Chiang Mai Province, Thailand. Qualitative content analysis identified key themes and patterns in participants’ experiences. Results Three major themes emerged: navigating physical changes and the pregnancy's effect on nursing practice; managing professional duty and workplace pressures; and workplace support structures and policy gaps. Discussion Pregnancy‐related physical and emotional changes heightened the challenges of clinical work, especially in high‐demand units. While support from colleagues and family helped lessen these burdens, many nurses reported limited formal adjustments and inconsistent managerial responses, which increased stress and affected their perceived safety at work. Conclusions Thai nurses working during pregnancy face significant challenges with insufficient structural and policy support to ensure safe and sustainable practice. Implications for Nursing Nursing administrators should adjust workloads, minimize occupational hazards, and provide clear guidance and training to promote equitable practices that protect maternal health and foster a supportive environment. Implications for Nursing Policy Strengthened maternity protection policies, flexible job adjustments, and defined institutional support systems may contribute to safeguarding pregnant nurses’ well‐being and promote safer workplaces.